Oracle WebLogic server 12c advanced administration cookbook : over 60 advanced recipes to configure, troubleshoot, and tune Oracle WebLogic server - Iwazaki, Dalton (Packt Publishing, 2013)
If you want to extend your capabilities in administering Oracle WebLogic Server, this is the helping hand you've been looking for. With 70 recipes covering both basic and advanced topics, it will provide a new level of expertise. Learn how to set a WebLogic environment with stability, high availability and performance Premature optmization is the root of all evil. Configure and tune only what really matters. Understand what are you doing and why. Every recipe covers the theory behind the practice. In Detail Oracle WebLogic Server is the core application server product of the Oracle Fusion Middleware platform. It is the premier application server for enterprise applications and has now been updated to 12C. If your company or client uses Oracle technology then you must know how to administer the Oracle WebLogic Server Oracle WebLogic Server 12c Advanced Administration Cookbook guides you through 70 recipes covering from the basics of WebLogic 12c installation, and passing through JDBC, JMS, cluster configuration and tuning. The book covers the day-by-day tasks of a WebLogic Administrator, enhanced with a lot of tips to build a WebLogic production environment focused on stability, high availability and performance. The best place to start with any book is at the beginning so the first thing that is covered is the basics. This quick refresher should get you back up to speed with WebLogic server and get you in the right frame of mind to get stuck into the more complex techniques. Each chapter then covers a specific topic with complex solutions simplified and explained. This is not only a book that guides you through complex techniques but also ensure you have a solid understanding of the theory behind the techniques. We dive into high availability clusters, configuring JMS and JDBC, and then moving on to more general WebLogic Server aspects. Monitor, troubleshoot, and tune the performance of your WebLogic server with time tested solutions. If you want to take your WebLogic server to the next level of performance and security or simply just want to be more in control this book is full of solutions that will allow you to achieve that aim.